ANALISIS IMPLEMENTASI PSAK 105 AKUNTANSI PEMBIAYAAN MUDHARABAH PADA BANK MUAMALAT CABANG BANDA ACEH - Putra, Dwi Andika; Arfan, Muhammad (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
This study aims to find out how the mudharabah financing mechanism at Bank Muamalat Banda Aceh and whether the application of mudharabah accounting treatment at Bank Muamalat Banda Aceh is in accordance with PSAK 105. The research methodology used is a qualitative method using descriptive analysis techniques that provide an overview of the treatment mudharabah financing accounting at the Bank Muamalat Banda Aceh. The results of the analysis state that the accounting treatment of mudharabah financing at the Bank Muamalat Banda Aceh has been carried out well because the recording of transactions has been carried out in accordance with Financial Accounting Standards. However, at the beginning of the application of accounting, the recognition of the mudharabah contract was not regulated in PSAK 105. However, at that time the Bank Muamalat Banda Aceh recognized it first as an obligation because there had not yet been capital surrender to mudharib. In the application of accounting when recognition of purchases for acquisition prices is not regulated in PSAK 105. Bank Muamalat Banda Aceh recognizes it as an additional inventory. Mudharabah financing procedures at Bank Muamalat Banda Aceh are quite good and thorough so as to minimize the risk of financing. Starting from the request for financing, BI checking, decisions, realization, monitoring up to repayment to the bank as the owner of the funds